First complete mitochondrial genome data of Hydrophilus bilineatus deciphered within the genus Hydrophilus - Nakasako Juiki; Ohara Daiki; Himeyuri Sunahata; Oda Rikuto; Nagano Sotaro; Fujimoto Erina; Tamura Naoya; Takuya Kiyoshi; Shin-ya Ohba; Jun-ichi Takahashi (Data in Brief)
Hydrophilus bilineatus (Coleoptera: Hydrophilidae) is an aquatic beetle species belonging to the family Hydrophilidae. In this study, the complete mitochondrial genome of H. bilineatus was sequenced, assembled, and annotated. The mitochondrial genome was 17,289 bp in length, with an AT content of 72.8 %. It consisted of 37 genes, including 13 protein-coding genes, 22 transfer RNA genes, and two ribosomal RNA genes. The nucleotide composition was A: 40.8 %, T: 32.0 %, C: 16.8 %, and G: 10.4 %. A phylogenetic analysis was conducted using 13 mitochondrial protein-coding genes from H. bilineatus and eight related hydrophilid species. The resulting tree is presented to show the mitochondrial gene-based relationships within Hydrophilidae.